NUTRIENT SOLUTIONS TO INDUCE CHANGES IN CONCENTRATION OF N, P, K IN MANGO PLANTS - López-Ordaz Anselmo; Baca-Castillo, Gustavo Adolfo; Fernández-Pavía Yolanda Leticia (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to compare two groups of nutrient solutions, these were studied by the Steiner nutrient solution or Hoagland-Hewitt changes in the concentrations of N, P and K in plants of mango (Mangifera indica L.) cv. Haden, of six months, induced by applying at a group of Steiner solutions and another group Hoagland-Hewitt low levels (deficiency), sufficient and high (toxicity) of N, P and K. The experiment was conducted in a greenhouse located in Lomas de San Esteban, Texcoco, Mexico, the plants were purchased and laid in a period of adjustment from March 15th to July 23th and, the treatments were applied from July 24th to November 23th, 2008. The plants were grown in a hydroponic system by sub-irrigation, as substrate, porous volcanic rock (tezontle) was used. We used a full factorial design of treatments 3∗3∗2 with four replicates. With the solutions of the Steiner group, regardless of their level of N, P or K in the nutrient solution, similar concentrations of N, P or K were obtained in the leaves and young stems, specifically in the interaction contrasts obtained from the N∗P∗K compound. By contrasting, through the interaction just indicated, the effect of Hewitt solution for toxicity, with the Hoagland solution for deficiency, there was a significant difference between the concentrations of N and P in the leaves and young stems. This effect was not gotten in the K concentration in the young stem.